2021
DOI: 10.3390/plants10050915
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Conditions for the Cultivation of Callus Cultures of Hyssopus officinalis Regarding the Yield of Polyphenolic Compounds

Abstract: The cultivation of plants in the form of callus cultures constitutes a renewable source of secondary plant metabolites. The conditions for the cultivation of callus cultures affect the yield of target compounds. Callus cultures of Hyssopus officinalis were chosen for study. Nutrient media of various compositions were used for Hyssopus officinalis callus culture. For each culture, data on the quantitative contents of saponins, flavonoids and polyphenolic compounds, as well as antioxidant activity, were obtained… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…Individual BAS samples were obtained by separating the Cotinus coggygria extract on a glass chromatographic column by preparative HPLC using a Shimadzu LC-20AD chromatograph (Shimadzu, Kyoto, Japan) and a high-pressure steel column with a sorbent size of 2.5 μm, a diameter of 2.5 mm, and a length of 250 mm [ 22 ]. Elution conditions: flow rate 1 mL/min; eluent water: methanol: 0.1% trifluoroacetic acid with a linear gradient from 40% to 90% methanol in 20 min; detection at a wavelength of 254 nm.…”
Section: Methodsmentioning
confidence: 99%
“…Individual BAS samples were obtained by separating the Cotinus coggygria extract on a glass chromatographic column by preparative HPLC using a Shimadzu LC-20AD chromatograph (Shimadzu, Kyoto, Japan) and a high-pressure steel column with a sorbent size of 2.5 μm, a diameter of 2.5 mm, and a length of 250 mm [ 22 ]. Elution conditions: flow rate 1 mL/min; eluent water: methanol: 0.1% trifluoroacetic acid with a linear gradient from 40% to 90% methanol in 20 min; detection at a wavelength of 254 nm.…”
Section: Methodsmentioning
confidence: 99%
“…In addition, some active ingredients and secondary compounds have successfully been produced by application of tissue culture approach using intact plants ( Figure 4 ). The examples are as listed: phenolic molecules, including apigenin, p-coumaric acid, genistein, luteolin, rutin hydrate, trans-ferulic acid, salicylic acid and naringenin from Coryphantha macromeris ( Karakas and Bozat, 2020 ); medicinally vital phenolic and flavonoid compounds, including apigenin, caffeic acid, catechin, gallic acid, hederagenin, myricetin, kaempherol, isorhamnetin, nahagenin, ursolic acid, betulinic acid from Fagonia indica ( Khan et al., 2019 ); p-coumaric acid, hesperidin, cafeic acid, rosmarinic acid from Rosmarinus officinalis ( Coskun et al., 2019 ); phenolics, including gallic acid, chlorogenic acid, caffeic acid, rutin, myricetin, quercetin, vanillic acid, luteolin and iso-rhamnetin, from Lycium barbarum ( Karakas, 2020 ); gingerol, shogaol, and zingerone from Zingiber officinale ( Arijanti and Suryaningsih, 2019 ); indole alkaloids, including echitamine, acetylechitamine, tubotaiwine and picrinine from Alstonia scholaris ( Jeet et al., 2020 ); crocin from Crocus sativus ( Moradi et al., 2018 ); anticancer alkaloids (vincristine and vinblastine) from Catharanthus roseus ( Mekky et al., 2018 ); phenylethanoid (salidroside, tyrosol), phenylpropanoid (rosavin and rosarin) and phenolic acids (p-coumaric acid, gallic acid, and cinnamic acid) from Rhodiola imbricata ( Rattan et al., 2020 ); eugenol and ursolic acid from Ocimum tenuiflorum ( Sharan et al., 2018 ); bioactive compounds, including 1,2-benzenedicarboxylic acid (phthalic acid), 3,7,11,15-tetramethyl-2-hexadecen-1-ol, 2-hexadecen-1-ol-3,7,11,15-tetrametil, hexadecanoic acid methyl ester (methyl palmitate), n-hexadecanoic acid (palmitic acid), 9,12-octadecadienoic acid methyl ester, 9,12,15-octadecatrienoic acid methyl ester, phytol, octadecanoic acid methyl ester (methyl stearate), 9,12,15-octadecatrienoic acid (linolenic acid) and squalene from Mucuna pruriens ( Sweetlin and Daniel, 2020 ); several different metabolics, including acetamide, propanoic acid, α-thujene, linalool, 5-hydroxymethylfurfural, β-maaliene, epidolichodial, calarene, seychellene, α-curcumene, eremophilene, α-vatirenene, valencene, α-cadinol, ledol, meso-erythritol, α-gurjunene, viridiflorol, (-)-globulol, spirojatamol, dodecanoic acid, patchouli alcohol, jatamansone, xylitol, aristolone, protocatechuic acid, mannose, hexadecanoic acid, p-coumaric acid, talose, α-D-mannopyranose, α-D-galactopyranoside, D-mannitol, myo-inositol, -D-glucopyranoside, D-(+)-trehalose, D-(+)-cellobiose, melibiose, vitamin E, β-sitosterol from Nardostachys jatamansi ( Bose et al., 2019 ); identified 11 organic acids, 16 phenolic acids, 8 flavonoids, and 17 metabolites of different classes from Coryphantha macromeris ( Cabanas-Garcia et al., 2021 ); phenolic compounds (ferulic acid, isoquercitrin, rutin, quercetin, quercetin-7-O-glucoside and luteolin) from Hyssopus officinalis ( Babich et al., 2021 ) and phenylethanoids and st...…”
Section: Tissue Culture-based Biotechnological Approaches For Obtaini...mentioning
confidence: 99%
“…Root segments were transferred in the laminar air flow hood into 250 mL Erlenmeyer flasks, filled with 100 mL of MS liquid medium supplemented with 5.4 µM α-naphthaleneacetic acid (NAA), 0.5 µM kinetin, and 30 g/L sucrose (pH: 5.8). It has been reported that the combined application NAA + kinetin helps in the production of saponins, flavonoids, and polyphenolic compounds [24][25][26]. The liquid root cultures were placed on a continuous rotary shaker (120 rpm) in a growth chamber (24 h dark, 22 ± 1 • C).…”
Section: Plant Materials and In Vitro Culture Conditionsmentioning
confidence: 99%